Outcome of Surgical Decompression in Simple Degenerative Lumbar Canal Stenosis - Paudel, Byapak; Chhabra, Harvinder Singh; Pradhan, Rabindra Lal; Arora, Mohit (Nepal Orthopaedic Association Journal, 2014)
Introduction: A sensory or motor deficit occurs in about half of patients with symptomatic lumbar canal stenosis. There is no study evaluating neurologically deficient patients with simple degenerative lumbar canal stenosis using validated measures and there are no consensus about outcome predictor of surgical decompression is available in literature. Only one study assessed outcome of patients with neurological deficit but it had not excluded either patients with comorbid conditions that affect outcome or those with lumbar canal stenosis secondary to spondylolisthesis and scoliosis. The aim of this study was to assess overall result and to compare the surgically treated patients of simple degenerative lumbar canal stenosis using validated outcome measures like Oswestry Disability Scale (ODS), Neurogenic Claudication Score (NCS), Visual Analogue Scale (VAS) and Satisfaction, this study also aimed to find outcome predictor of surgical decompression. Methods: This was a retrospective comparative study with homogenous cohorts with control of comorbid conditions that affect outcome. Each cohort ( Those with neurological deficit and without neurological deficit) had 11 patients who had adequate decompression with laminectomy and foraminotomies. Outcome was evaluated using validated ODS, NCS, VAS and Satisfaction in overall and also evaluated by each section of ODS, NCS with appropriate statistical analysis of both cohorts. Results: Neurologically deficient patients had more back pain, tingling, numbness, weakness and heaviness preoperatively. In neurologically deficient patients there was a trend to have poorer outcome, but overall recovery rate was higher than neurologically normal patients. Sensory deficit did not recover. The index surgery may not have effect on sitting and sleeping in both cohorts and may not have effect on lifting in neurologically normal patients and may not have effect on social life in neurological deficient patients. Additionally the index surgery may not have effect in relieving symptoms of numbness, tingling and heaviness and weakness in neurologically normal patients and may not have effect on standing in both cohorts. Recovery according to VAS was higher in neurologically normal patients. Preoperative NCS and preoperative heaviness and weakness severity contributed up to 43 % in ODS recovery rate. Conclusion: Overall there is a trend to have poorer outcome in neurologically deficient patients though recovery rate is better than neurologically normal patients. Recovery in term of VAS is better in neurologically normal patients. Preoperative NCS and preoperative heaviness and weakness severity score predict or contribute up to 43 % in ODS recovery rate. DOI: http://dx.doi.org/10.3126/noaj.v3i2.9512 NOAJ July-December 2013, Vol 3, Issue 2, 2-9